Reasons given by pregnant women for participating in a clinical trial aimed at preventing premature delivery: a qualitative analysis - Thaís M. Monteiro; Leila Katz; Silvana F. Bento; Melania M. Amorim; Patrícia C. Moriel; Rodolfo C. Pacagnella (BMC, 2019)
Abstract Background In clinical trials, pregnant women are potentially vulnerable, and the fetus is exposed to the intervention. This study aimed to identify the reasons that led pregnant women at a high risk of premature delivery to participate in a randomized clinical trial. Methods The women participating in the main trial were contacted by telephone postpartum and invited to answer an open questionnaire in a cross-sectional study. Data were collected by telephone and analyzed using thematic analysis. After the analysis categories were defined, all the answers were reviewed, categorized and grouped. A descriptive summary of the content of each category was then made. Results Overall, 208 women from different geographical regions of the country agreed to participate. Four categories were identified: 1) The risk of losing the baby; 2) A previous experience of premature delivery; 3) The role of the doctor and other health professionals, and 4) The availability of quality medical care and free medication. The main reason given for agreeing to participate was to reduce the risks associated with the baby being born prematurely, particularly when the woman herself or someone close to her had already experienced premature delivery. Other reasons were having received clear guidance and explanations from the doctor regarding prematurity and about the study and being given the opportunity to receive free treatment with greater access to the public healthcare system. Conclusions The decision to participate in a clinical trial is not easy, particularly when the individual is vulnerable and in a critical situation as in the case of a pregnant woman at a high risk of delivering prematurely. Fears and uncertainties regarding the pregnancy outcome, as well as the woman's previous experiences and her awareness of the actual risks she faces will affect her decision regarding whether or not to participate. Recruitment challenges could be overcome by ensuring that the research team provides adequate information and support, thus creating a bond with participants that would foster a sense of safety and trust in the study proposals.